Analysis of the Potential of Fresh Fruit Health Drink Agroindustry for Creative Food Business Education for Agricultural Students in Manado City - Herry F. Pinatik; Dedie Tooy; David P. Rumambi; Mukhlis (Postgraduate, University of Mataram, 2025)
This study aims to determine the potential of fresh fruit juice health drink agro-industry financially, namely 1). Determine the revenue, cost and profit of fresh fruit juice agro-industry business, by R/C Ratio value, 2). Determine the development strategy of fresh fruit juice health drink processing agro-industry from local fresh fruit raw materials, 4). Knowing the impact of agro-industry of fresh fruit juice health drinks for the education of agricultural students as a food technology business. This study used two analysis method approaches, namely financial business income analysis and SWOT analysis (Strength, Weakness, Opportunities, Threats). The results showed that agro-industrial activities of fresh fruit juice health drinks by sario fresh fruit shop traders in Manado city provide financial benefits, namely: 1). The average total revenue per production per month amounted to IDR 17,700,000, with a total cost of expenditure per production of IDR 9,501. 248, and total profit of IDR 7,498,752 per production; 2). The R/C Ratio value of 1.28 means that the fresh fruit juice agro-industry business is feasible; 3). The strategy for developing the fresh fruit juice health drink agro-industry, in order to maintain financial benefits, includes: a) increasing the amount of production of various fresh fruit juices; b) improving the quality of both the natural color of the fruit, smell and taste, without preservatives; and c) enlarging business capital, and making production efficiency to meet local and national market demand. 3) Agroindustry of fresh fruit juice health drinks actually provides education that the food technology business in addition to teaching materials for agricultural technology entrepreneurship (technopreneurship) and agroindustry management also fosters creative food entrepreneurs to UNSRAT Manado agriculture students.